Who's who of British jazz - Chilton, John, 1931- (Cassell, 1997)
In this comprehensive survey, John Chilton brings his world renowned research skills to assembling the first ever full-length reference work devoted to the biographies of British jazz musicians. In over 850 career summaries he details the work of musicians from every era of British jazz, ranging from those who played professionally before 1920 at the dawn of jazz in Britain, through to today's young stars. Much new information is revealed on the early careers of those who became famous and the chronological listing of events in each subject's life sheds new light on the development of jazz in the United Kingdom.